Rasch Analysis Model: Reliability and Validity of Superitem Test Instrument - Ridzuan, Mohd Faizul; Lian, Lim Hooi; Ahmad Fozee, Farah Atiqah; Mohd Nasser, Siti Nur Anissa (International Journal of Academic Research in Progressive Education and Development, 2020)
This study is conducted to measure the reliability and validity of superitem test based on Rasch Analysis Model. Superitem test instrument is built based from SOLO Model four hierarchical levels namely unistructural, multistructural, relational and extended abstract. There are four content domains of linear equations tested in superitem test which are linear pattern (pictorial), direct variation, concept of function and arithmetic sequence. Every correct response made by the students involved are references to any stages in SOLO Model which also shows their algebraic solving ability. This research is conducted among community college in Perak state that involved 390 respondents. The results demonstrated the individual reliability is high at 0.90 with separation index of 2.98 whereas the item realibility is also high at 0.99 with separation index of 9.41. Besides that, superitem test has fulfilled the validity aspect construction in Rasch Analysis Model in terms of item fit, polarity item and unidimensionality. In conclusion, superitem test instrument is valid and able to measure algebraic solving ability in community college students.